2011
DOI: 10.1007/s10337-011-2002-x
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Structures of Metabolites of Picroside II in Rat Bile by LC–ESI–IT–MS

Abstract: Picroside II is one of the main active constituents of Picrorhiza kurroa, which has hepatoprotective, anticholestatic, antioxidant, and immune-modulating activity. To gain an understanding of the biotransformation of picroside II in vivo, liquid chromatography-electrospray ionization ion-trap mass spectrometry (LC-ESI-IT-MS) was used to investigate the metabolism of picroside II in rats after intravenous administration of a single dose. This method could simultaneously determine picroside II and its metabolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…These results indicate that M7 and M8 may be M5 (picroside II) glucuronide and M6 (isovanilloylcatalpol) glucuronide, respectively, but the position of glucuronidation was not accurately identified. These results support the results of Li et al [ 10 ] that identified picroside II glucuronide in the bile samples obtained after intravenous administration of picroside II in rats.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These results indicate that M7 and M8 may be M5 (picroside II) glucuronide and M6 (isovanilloylcatalpol) glucuronide, respectively, but the position of glucuronidation was not accurately identified. These results support the results of Li et al [ 10 ] that identified picroside II glucuronide in the bile samples obtained after intravenous administration of picroside II in rats.…”
Section: Resultssupporting
confidence: 92%
“…Sulfatase treatment of the bile and urine samples increased the peak areas of M5 (picroside II) and M6 (isovanilloylcatalpol), but decreased the M9 and M10 peaks. These results indicate that M9 and M10 might be M5 (picroside II) sulfate and M6 (isovanilloylcatapol) sulfate, respectively, supporting the result of Li et al [ 10 ] that showed picroside II was metabolized to picroside II sulfate as well as picroside II glucuronide in rats.…”
Section: Resultssupporting
confidence: 88%
“…M01, M02 and M09 were found as the circulating metabolites in rat plasma, which may be associated with its activity. Although the biotransformation on picroside II have been reported in previous studies [23][24], our observations provided insights into the in vivo disposition of picroside II as a total of six metabolites were newly identified (M03-M08). Further studies should focus on the preparation of the newly identified principal metabolites and the evaluation of their hepatoprotective effects and toxicities.…”
Section: Metabolic Profiles Of Picroside II In Ratsmentioning
confidence: 85%
“…To confirm this M3 was incubated with sulfatase, 10 which hydrolyzed M3 into (+)À1. The NMR (both 1 H and 13 C) of (+)À1, which was obtained via the action of sulfatase on M3 was identical to that of (À)À1, which was obtained via the hydrolysis of M1 (see Scheme 1).…”
mentioning
confidence: 99%